FRED: a fast Monte Carlo code on GPU for quality control in Particle Therapy. (May 2020) - Simoni, M De; Fischetti, M; Gioscio, E; Marafini, M; Mirabelli, R; Patera, V; Sarti, A; Schiavi, A; Sciubba, A; Traini, G
Abstract: Charged Particle Therapy is a non-invasive technique for radio-resistant tumor treatment performed with protons or light ions, aiming to deliver a high precision treatment. Compared to conventional radiotherapy, ions allow for a higher dose deposition in the tumor region while sparing the surrounding healthy tissue. To really exploit the potential benefits of this technique, the highest possible accuracy in the calculation of dose and its spatial distribution is required in treatment planning. Commonly used Treatment Planning Software solutions adopt a simplified beam-body interaction model. An alternative is the use of Monte Carlo simulations which explicitly take into account the interaction of charged particles with actual human tissues hence providing highly accurate results. However, Monte Carlo simulations are used in a restricted number of cases due to substantial computational resources required. The code FRED has been developed to allow a fast optimization of the treatment plans in Charged Particle Therapy while profiting from the dose release accuracy of a Monte Carlo tool. Currently, the most refined module is the transport of proton beams in water. A comparison with measurements shows that the lateral dose tails are reproduced within 2% in the field size factor test up to 20 cm. Models for the interaction of ion with the matter are currently under development in the FRED code. The status of new developments and the performance of FRED will be presented.